Important Drawings Watercolours and Graphics of the 19th and 20th Centuries. (London : Marlborough Fine Art Ltd., 1971)
Braque, Georges ; Chagall, Marc ; Daumier, Honoré ; Feininger, Lyonel ; Gleizes, Albert ; Guys, Constantin ; Kandinsky, Wassily ; Klee, Paul ; Kokoschka, Oskar ; Leger, Fernand ; Mondriaan, Piet ; Moore, Henry ; Munch, Edvard ; Nolde, Emil ; Picasso, Pablo ; Renoir, Pierre Auguste ; Rouault, Georges ; Signac, Paul ; Sutherland, Graham ; Vuillard, Edouard
Engels
Important Drawings Watercolours and Graphics of the 19th and 20th Centuries, Marlborough Fine Art Ltd., London, March - April 1971
boek